Utility of a Liquid Formulation of Levo-thyroxine in Differentiated Thyroid Cancer Patients - Giusti, M.; Mortara, L.; Machello, N.; Monti, E.; Pera, G.; Marenzana, M. (Drug Research, 2015)
The goal of levo-thyroxine (L-T4) administration in differentiated thyroid cancer (DTC) is to suppress thyroid stimulating hormone (TSH) levels. The tolerability and efficacy of a new formulation of liquid L-T4 vs. the previous tablet formulation was evaluated in a cohort of 59 patients with cured DTC. The correlation between breakfast modality and therapy was also monitored. Hormonal and clinical evaluations were performed before and 70 days after patients were switched from tablet to liquid L-T4 formulation, without changes in daily dose. Breakfast habits were evaluated. The interval between L-T4 therapy and breakfast was recorded. Patient approval of L-T4 formulations was evaluated. 8% of patients dropped out owing to adverse events. The modality of L-T4 administration proved adequate under tablet and liquid formulation in 64% and 68% of patients who fully complied with the protocol. While significantly more patients found the tablet formulation more agreeable, at the end of the protocol subjective symptoms had diminished significantly and 73% requested to remain on the liquid formulation. No change in TSH, thyroid hormones or thyroglobulin was noted during the study. A balanced breakfast containing less than 4 g of alimentary fibre did not interfere with L-T4 therapy. Liquid L-T4 seems to be a valid alternative formulation in DTC patients, its initial dislike being outweighed by a significant reduction in subjective symptoms. Both tablet and liquid L-T4 therapy require monitoring over time. A continental breakfast containing less than 4 g of alimentary fibres seems to favour the absorption of L-T4, whether in tablet or liquid formulation.
Keywords: liquid L-T4; differentiated thyroid cancer; continental breakfast